A NEGLIGÊNCIA GOVERNAMENTAL: O ABANDONO ESTATAL NA ALOCAÇÃO DE RECURSOS PARA INVESTIGAÇÕES DOS CRIMES DE HOMICÍDIO (REMUNOM, 2024)
This study addresses the worrisome lack of homicide resolution in some Brazilian states, attributing it to government negligence in the preservation of evidence at the crime scene and insufficient investments in investigative procedures such as chain of custody, forensic examination, and technical expertise. Homicide, as the most serious crime, emerges as one of the main forms of violence, violating the right to life enshrined in the Federal Constitution. The low rate of resolution of these cases results in impunity and challenges the punitive power of the state. The objectives of the study include understanding the reasons for the lack of clarification of homicides, investigating the importance of investigative procedures, and examining how the government can invest in these investigations to prevent impunity. The methodology adopted consists of exploratory and descriptive bibliographic research, using sources such as scientific articles and research data from 2014 to 2023. The study seeks to contribute to the understanding of the lack of clarification of homicides and highlight the need for effective investments and policies to combat impunity in violent crimes.